On σ(∙,W)-holomorphic functions and theorems of Vitali-type - Thai Thuan Quang; Lien Vuong Lam; Nguyen Van Dai (My University, 2013)
On σ(∙,W)-holomorphic functions and theorems of Vitali-type
Keywords: Holomorphic functions; Vitali-type theorems; σ(∙,W)